The molecular basis of memory. Part 3: tagging with “emotive” neurotransmitters - Marx, Gerard; Gilon, Chaim (Frontiers in Aging Neuroscience, 2014)
Many neurons of all animals that exhibit memory (snails, worms, flies, vertebrae) present arborized shapes with many varicosities and boutons. These neurons, release neurotransmitters and contain ionotropic receptors that produce and sense electrical signals (ephaptic transmission). The extended shapes maximize neural contact with the surrounding neutrix (neural extracellular matrix (nECM)+ diffusible (neurometals and neurotransmitters) as well as with other neurons. We propose a tripartite mechanism of animal memory based on the dynamic interactions of splayed neurons with the “neutrix”. Their interactions form cognitive units of information (cuinfo), metal-centered complexes within the nECM around the neuron. Emotive content is provided by NTs, which embody molecular links between physiologic (body) responses and psychic feelings. We propose that neurotransmitters form mixed complexes with cuinfo used for tagging emotive memory. Thus, NTs provide encoding option not available to a Turing, binary-based, device. The neurons employ combinatorially diverse options, with > 10 NMs and > 90 NTs for encoding (“flavoring”) cuinfo with emotive tags. The neural network efficiently encodes, decodes and consolidates related (entangled) sets of cuinfo into a coherent pattern, the basis for emotionally imbued memory, critical for determining a behavioral choice aimed at survival. The tripartite mechanism with tagging of NTs permits of a causal connection between physiology and psychology.